PENYULUHAN DENGAN PENDEKATAN WILAYAH GUNA MEWUJUDKAN DESA SEBAGAI PUSAT PERTUMBUHAN DI KABUPATEN GUNUNGKIDUL (AGRICULTURAL EXTENSION THROUGH AREA APPROACH TO CONSTRUCT VILLAGES AS GROWTH CENTRE IN GUNUNGKIDUL REGENCY) - Hariadi, Sunarru Samsi (Politeknik Pembangunan Pertanian Yogyakarta-Magelang, 2006)
Gunungkidul regency has three zones/ areas; north, middle, and south, every zone has specific agricultural potency. For developing villages as economic growth centre, agricultural extension has to be conducted through area approach with pay attention to potency of local agriculture. Product quality and quantity of local agriculture ought to be improved, then develop agricultural product industry, matching with local area to construct excursion place.